1996
DOI: 10.1046/j.1471-4159.1996.66020604.x
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Glia Exhibit P2U Receptors that Increase Cytosolic Calcium by a Phospholipase C‐Dependent Mechanism

Abstract: Calcium signaling in fura-2 acetoxymethyl ester-loaded enteric glia was investigated in response to neuroligands; responses to AlP were studied in detail. Carbachol (1 mM), glutamate (100 jiM), norepinephrine (10 jiM), and substance P (1 pM) did not increase the intracellular calcium concentration ([Ca 24 ],) in cultured enteric glia. An increasing percentage of glia responded to serotonin (4%; 100 pM), bradykinin (11%; 10 1eM),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
3
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 36 publications
6
65
3
1
Order By: Relevance
“…Second, although guinea pig enteric glia express mGluR5 receptors, stimulation with mGluR agonists (in our hands) does not initiate glial calcium responses (our unpublished observations). In agreement with our findings in situ, Kimball and Mulholland (1996) reported that cultured guinea pig myenteric glia do not respond to glutamate. We also fail to detect enteric glial calcium responses to norepinephrine and muscarinic receptor agonists (our unpublished observation).…”
Section: Discussionsupporting
confidence: 93%
“…Second, although guinea pig enteric glia express mGluR5 receptors, stimulation with mGluR agonists (in our hands) does not initiate glial calcium responses (our unpublished observations). In agreement with our findings in situ, Kimball and Mulholland (1996) reported that cultured guinea pig myenteric glia do not respond to glutamate. We also fail to detect enteric glial calcium responses to norepinephrine and muscarinic receptor agonists (our unpublished observation).…”
Section: Discussionsupporting
confidence: 93%
“…All cells responded with D[Ca] i characteristic of this agonist (Kimball and Mulholland 1996). These results are in accordance with previous observations in which primary exposure to the enzyme (thrombin or trypsin) renders the receptor non-responsive to successive agonist exposure.…”
Section: Receptor Desensitizationsupporting
confidence: 92%
“…As seen in Fig. 10c and previously reported (Kimball and Mulholland 1996), the vast majority of the cells in the culture were glial cells. As a negative control, primary antibodies were replaced with antibody solvent (2% serum in phosphate-buffered saline).…”
Section: Detection Of Par By Immunofluorescencesupporting
confidence: 86%
See 2 more Smart Citations